Styrax rhytidocarpus (Styracaceae), a new species from Hunan, China - Zhou, Hui; Yang, Wen; Li, Ming; Yu, Xun-Lin (Phytotaxa, 2015)
A new species, Styrax rhytidocarpus W. Yang & X. L. Yu (Styracaceae) from Hunan, China, is described and illustrated. This species can be readily distinguished from all other species of Styrax by the combination of characters: glabrous peduncles, bracteoles, and pedicels; 1.7–2.0 × 0.8–1.3 cm corolla lobes; bowl-shaped and deeply rugose persistent calyx; thick, fleshy, and rugose fruit with slightly curved and long-rostrate apex; and ridged and densely stellate-hairy seeds.